Parental Contributions to Character Development in Primary Education - Fajri, Ahmad (Journal of Foundational Learning and Child Development, 2025)
Purpose of the study: This study aims to investigate the role of parents in supporting character education for primary school children in Bangkinang, Indonesia, and to identify effective strategies for parental involvement in character development. Materials and methods: A quantitative research design was employed, involving 186 parents of primary school children (grades 1-6) from five elementary schools in Bangkinang. Data were collected using a structured questionnaire measuring six dimensions of parental involvement in character education. Statistical analysis was conducted using IBM SPSS Statistics version 30. Results: The findings revealed that 78.5% of parents actively participated in their children's character education through various strategies. The most effective approaches included role modeling (M=4.32, SD=0.76), providing guidance (M=4.17, SD=0.84), and establishing consistent routines (M=3.98, SD=0.92). Significant differences were found between parental education levels and the implementation of character education strategies (p<0.05). Conclusions: The study concludes that parental involvement significantly contributes to character development in primary school children. Collaboration between parents and schools is essential for establishing effective character education. Parents who model positive behaviors, provide consistent guidance, and establish routines demonstrate the most effective approaches to character education